Outcome prognosticators in patients with severe traumatic brain injury - Modikeng, Cleopatra Lebohang (My University, 2016)
Background: Many Coma scales have evolved for the assessment of patients with Traumatic Brain Injury (TBI), but the widely used Glasgow Coma Scale (GCS) has limitations. These limitations can be overcome by the new Coma Scale called the Full Outline of UnResponsiveness score (FOUR). Objectives: The aim and objective of this study was to define and compare the GCS and the FOUR score in predicting in-hospital mortality, functional outcome at discharge by using the Glasgow Outcome Scale (GOS) in patients who sustained severe TBI. Methods: A cross sectional study was conducted in consecutive adult patients who were admitted in Chris Hani Baragwanath Academic Hospital and Charlotte Maxeke Johannesburg Academic Hospital between July and December 2015 with Severe Traumatic Brain Injury. A data sheet was used to collect study information. Results: 54 patients were recruited in the study, 93% (n=50) were male patients and most of the male patients were assaulted. The FOUR score of 6 and below predicted poor outcome whilst a FOUR score of 10 predicted good outcome. Conclusion: The FOUR score can be used together with the GCS for those patients who are intubated, as the FOUR score didn’t show much significant difference in predicting outcome.
A research report submitted in fulfilment of the requirements for the degree of Masters of Medicine in Neurological Surgery In the Faculty of Health Sciences University of the Witwatersrand Johannesburg, 2016